Microstructure and Crystallographic Texture in Twin-Roll Casting of AA1050 Aluminum Alloy: Simulation and Industrial Validation - ŞEREFOĞLU KAYA, MELİS (My University, 2022)
Twin-roll casting (TRC) is a process in which liquid metal is introduced directly between counter-rotating water-cooled rolls, where it solidifies and is rolled to a strip having final thickness of 3 to 8 mm. TRC for aluminum is best suited to those alloys having a narrow freezing range with little susceptibility to hot tearing, such as 1XXX, 3XXX, 5XXX, and 8XXX. TRC offers advantages over conventional DC casting followed by hot and cold rolling for these alloys due to its lower capital cost, and decreased downstream processing operational cost and energy consumption, since hot rolling is not required. The microstructure formed in the strip must be carefully controlled, because as a near-net shape product used mostly for non-age-hardenable alloys, there is limited opportunity to modify it by subsequent processing. In particular, the near-surface microstructure has a strong effect on performance in forming applications. In this article, we present a computational model of TRC, and validate it for AA1050 aluminum alloy in a production environment. The novel aspect of this work is that the model is used to predict the final microstructure and crystallographic texture of the cast strip. The model is validated in plant trials for strip cast at a range of thicknesses, casting speeds, and caster setup by comparing the predicted microstructure, texture, and process outcomes such as roll separating force and forward slip to their corresponding measured values. We then apply the validated model to explore process parameters outside the standard practices, including feed inlet setback, casting speed, metal inlet temperature, and changing roll material to demonstrate how the microstructure and texture can be controlled via these parameters. (C) The Minerals, Metals & Materials Society and ASM International 2022
Keywords: Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); METALURJİ VE METALURJİ MÜHENDİSLİĞİ; MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); METALLURGY & METALLURGICAL ENGINEERING; Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Fizik Bilimleri; Metals and Alloys; Materials Chemistry; General Materials Science; Physical Sciences